Neither Cue Familiarity nor Semantic Cues Increase the Likelihood of Repeating a Tip-of-the-Tongue State - L. Kathleen Oliver; Timmie Li; Jonathan J. Harley; Karin R. Humphreys (Collabra: Psychology, 2019)
Psycholinguistic and metacognition researchers mostly disagree on what constitutes a tip-of-the-tongue (TOT) state. Psycholinguists argue that TOT states occur when there is a transmission of activation failure between the lemma and phonology levels of word production (e.g., Burke, MacKay, Worthley, & Wade, 1991). Metacognition researchers argue that the TOT state is better described as a subjective experience caused by a mechanism that assesses the likelihood of recall from memory. One sub-hypothesis of the metacognitive account of TOT states is the cue familiarity hypothesis, which suggests that a TOT state may occur when cues elicit a feeling of familiarity (Metcalfe, Schwartz, & Joaquim, 1993). We conducted three experiments to evaluate the cue familiarity hypothesis of TOT state etiology. Experiment 1 included a test-retest TOT task with identical definitions (i.e., cues that should elicit familiarity) versus alternative definitions. TOTs were as likely to repeat for alternative definitions across test and retest as identical definitions, which is inconsistent with the cue familiarity hypothesis. Experiment 2 included the same task layout as Experiment 1, but we used very different cues (pictures versus descriptions for famous people). Again, we found that TOTs tended to repeat regardless of whether or not prompts were identical. In Experiment 3, we presented either a picture and description simultaneously or a description only on the first test, followed by a description only on retest. We found that giving participants an extra semantic cue did not change the probability of repeating a TOT state. These findings suggest that repeated TOT states do not occur due to cue familiarity nor is the locus of the TOT state at the semantic level of the word production/word recall system. Therefore, we argue that the results point towards a success of lemma access, but then failure of the lemma-to-phonology mappings.